2005
DOI: 10.1111/j.1365-3156.2004.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Earth-eating and reinfection with intestinal helminths among pregnant and lactating women in western Kenya

Abstract: SummaryWe conducted a longitudinal study among 827 pregnant women in Nyanza Province, western Kenya, to determine the effect of earth-eating on geohelminth reinfection after treatment. The women were recruited at a gestational age of 14-24 weeks (median: 17) and followed up to 6 months postpartum. The median age was 23 (range: 14-47) years, the median parity 2 (range: 0-11). After deworming with mebendazole (500 mg, single dose) of those found infected at 32 weeks gestation, 700 women were uninfected with Asca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 24 publications
12
61
0
10
Order By: Relevance
“…In two studies also conducted in Kenya, geophagy was associated with helminth infections in children. 23,24 This is consistent with the growing body of literature indicating that soil is an exposure route for enteric pathogens. [23][24][25][26] Furthermore, these findings suggest that geophagy may be a potential risk factor for EE and stunting in pediatric populations.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…In two studies also conducted in Kenya, geophagy was associated with helminth infections in children. 23,24 This is consistent with the growing body of literature indicating that soil is an exposure route for enteric pathogens. [23][24][25][26] Furthermore, these findings suggest that geophagy may be a potential risk factor for EE and stunting in pediatric populations.…”
Section: Introductionsupporting
confidence: 80%
“…[23][24][25][26]42 However, despite this growing evidence base, interventions to intervene upon this exposure route for pediatric populations are nonexistent. Furthermore, we found that in our study population that caregivers do little to prevent children from putting soil in their mouth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the substance must contain viable nematode eggs or larvae). An association between earth consumption and increased Trichuris and Ascaris burden in earth consumers has been shown in several (Geissler et al, 1998a;Luoba et al, 2005;Saathoff et al, 2002;Wong et al, 1991) but not all (Vermeer and Frate, 1979) studies. Yet, to date, measurement of the parasite content of the soil has been investigated in only two sites (Geissler et al, 1998a;Wong and Bundy, 1990;Wong et al, 1991), no studies have determined the parasite content of earth consumed by adults and no studies have looked at the parasitic content of non-earth pica substances.…”
Section: Introductionmentioning
confidence: 99%
“…Наряду с генетическими причинами могут рассматриваться некоторые психофизиологические механизмы, например, такие как геофагия [14]. Поскольку популяции Брестской и Витебской областей отличаются по содержанию характеристик ментальной сферы, то могут выстраиваться гипотетические цепочки между региональными психологическими характеристиками и особенностями эпидемиологического процесса.…”
Section: результаты и обсуждениеunclassified